(3EYOGO GdWad GdYQHj ddbQGAI hGdcJGHI (B/s - (3GdfGTa, gOi eMehOs 1936- ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ,s, 1999)
(3jJfGhd gPG GdcJGH ehVhY GdWad hGdbQGAI, hjJMOK Yf cjajI EYOGO GdWad GdYQHj ddbQGAI hGdcJGHI HGddZI GdYQHjI hJfejI egGQGJ GddZI GdbhejI HeG JeKdg ef bjeI KbGajI hhWfjI(B.s
Keywords: (3GdbQGAIs -- (3OQGSI hJYdje (B((3WahdI eHcQI(B)s